High Expression of SOX2 Is Associated with Poor Prognosis in Patients with Salivary Gland Adenoid Cystic Carcinoma - Dai, Wei (Molecular Diversity Preservation International (MDPI), 2014)
Sex determining region Y-BOX2 (SOX2), one of the key members of the SOX family, is a transcription factor that is involved in the maintenance of embryonic stem cell pluripotency and in multiple developmental processes. Recent studies have shown that SOX2 is aberrantly expressed in several types of tumors. The present study aimed to investigate the clinicopathological and prognostic significance of SOX2 in adenoid cystic carcinoma (ACC) of salivary gland. In this study, the expression of SOX2 in ACC tissues and matched adjacent non-cancerous tissues was measured by immunohistochemistry, western blot, and quantitative polymerase chain reaction. High SOX2 expression occurred in approximately 62.6% of primary ACC. In addition, high expression of SOX2 was significantly associated with T classification (p = 0.003) and distant metastasis (p = 0.002). The 5-year overall survival (OS) and disease-free survival (DFS) in patients with high SOX2 expression is poorer than those with low SOX2 expression. When adjusted by multivariate analysis, high SOX2 expression, together with distant metastasis, was an independent prognostic factor. The findings of the present study provide evidence that SOX2 represents a potential novel prognostic biomarker for ACC patients.